2008
DOI: 10.1007/s10545-008-0832-y
|View full text |Cite
|
Sign up to set email alerts
|

‘Non‐neuronopathic’ Gaucher disease reconsidered. Prevalence of neurological manifestations in a Dutch cohort of type I Gaucher disease patients and a systematic review of the literature

Abstract: Gaucher disease is a lysosomal storage disorder, which is classically divided into three types. Type I Gaucher disease is differentiated from types II and III disease by the absence of nervous system involvement. However, an increasing number of reports has emerged on neurological manifestations in patients with type I Gaucher disease. Whether a strict division in three different phenotypes is still valid has been the subject of debate. The main objective of this study was to provide scientific arguments wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 102 publications
1
59
0
5
Order By: Relevance
“…In addition, it should be clarified that the neurologic features in type I GD are different from those reported in the neuronopathic forms (type II and III), consisting mainly of peripheral neuropathy, Parkinsonism, and neurologic changes secondary to bone complications. 12 …”
Section: Classic Subtypes Of Gdmentioning
confidence: 99%
“…In addition, it should be clarified that the neurologic features in type I GD are different from those reported in the neuronopathic forms (type II and III), consisting mainly of peripheral neuropathy, Parkinsonism, and neurologic changes secondary to bone complications. 12 …”
Section: Classic Subtypes Of Gdmentioning
confidence: 99%
“…A recent systematic review of published literature identified 86 studies in which patients with GD1, or carriers of a glucocerebrosidase gene mutation, had some form of neurological manifestation (Biegstraaten et al, 2008;Cherin et al, 2010) contrary to the classical neuronopathic phenotypical description. Peripheral nervous system manifestations appear to be of particular relevance in GD1.…”
Section: Phenotype Continuum In Gaucher Diseasementioning
confidence: 99%
“…However the precise mechanisms by which glucosylceramide storage originate them is still unclear. The frequency of neurological GD cases is ranging between 7% and 17%, according to different series (Biegstraaten et al, 2008;Chérin et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Although the N370S mutation was considered to confer protection from neurological involvement, patients with this mutation may be at increased risk for parkinsonism 12,13 and/or may develop peripheral nerve abnormalities. 14,15 Type 2: acute perinatal lethal neuronopathic form Type 2 is a lethal neuronopathic form usually associated with compound heterozygosity for a severe mutation and a null mutation, [16][17][18] characterized by hypertonic posturing, strabismus, trismus, and retroflexion of the head during the first 6 months of life and death following aspiration pneumonia and/or apnea/laryngospasm by 2 years. 19 Massive hepatosplenomegaly and lung involvement are usually seen.…”
Section: Elstein and Zimran Dovepressmentioning
confidence: 99%